An optimal energy consuming protocol for localization using ANFIS residual energy for MANET - M, Vasim babu; R, Ramasamy (International Journal of Engineering and Technology, 2018)
In recent years, the scientific community has acquired a fair amount of recognition on Mobile Adhoc Networks (MANETs). These devices are used in wide range of application scenarios due to its compact size, affordable devices consumed scarce energy and finite computing resources .These application includes biomedical health monitoring, environmental monitoring and target tracking where node localization is essentially another system parameter. Localization of nodes is mandatory in order to detail the emergence of events, routing and to respond queries regarding network coverage, oblige group enquiring of sensors. In this paper, a competent protocol is proposed that consumes less energy of nodes in MANET which is based on ANFIS residual threshold energy. The threshold value is determined based on the fuzzy membership functions. Primarily the neighborhood nodes of source are formulated using two factors: enclosed region and relaying region. The neighbor nodes deliberated by those factors adopt the maximum threshold value initiated using ANFIS. The node with maximum values of threshold and distance is preferred as the next hop for the transaction. The experimental outcome interprets that our protocol can prominently diminish the overall energy consumption considering for all environments.